Analytic methods for Diophantine equations and Diophantine inequalities - Davenport, Harold, 1907-1969 (Cambridge mathematical library., 2005)
"Harold Davenport was one of the truly great mathematicians of the twentieth century. Based on lectures he gave at the University of Michigan in the early 1960s, this book is concerned with the use of analytic methods in the study of integer solutions to Diophantine equations and Diophantine inequalities. It provides an introduction to a timeless area of number theory that is still as relevant today as it was when the book originally appeared."--Jacket